A turbo FDE technique for reduced-CP SC-based block transmission systems - Gusmão, António (2010)
For conventional cyclic-prefix (CP)-assisted block transmission systems, the CP length is selected on the basis of the expected maximum delay spread. With regard to single-carrier (SC)-based block transmission implementations, a full-length CP is recommendable, since it allows good performances through the use of simple frequency-domain equalization (FDE) techniques. In this letter, a soft-decision-directed correction (SDDC)-aided turbo FDE technique is presented for reduced-CP SC-based block transmission systems using conventional frame structures. The relations with some already known iterative FDE techniques are established, and a set of performance results is reported and discussed. The advantages of the proposed approach are emphasized, namely, the possibility of approximately achieving (besides the obvious bandwidth efficiency gain) the maximum power efficiency gain that a strong CP reduction allows.